A polysaccharide from Polygonatum sibiricum attenuates amyloid-β-induced neurotoxicity in PC12 cells. (6th March 2015) - Zhang, Huixue; Cao, Yuze; Chen, Lixia; Wang, Jianjian; Tian, Qinghua; Wang, Ning; Liu, Zhaojun; Li, Jie; Wang, Na; Wang, Xiaokun; Sun, Piyun; Wang, Lihua
Highlights: A polysaccharide (PS-WNP) was purified from Polygonatum sibiricum . Protective effect of PS-WNP against Aβ25–35 -induced neurotoxicity in PC12 cells was examined. PS-WNP pretreatment attenuated Aβ25–35 -induced apoptosis in PC12 cells. PS-WNP protected PC12 cells against Aβ25–35 -induced apoptosis via PI3K/Akt signaling pathway. Abstract: One of the pathological hallmarks of Alzheimer's disease (AD) is the progressive accumulation of beta-amyloid (Aβ) in the form of senile plaques, and Aβ induced neurotoxicity has been identified as a major cause of the onset of AD. In this study, we investigated the protective effects of a polysaccharide (PS-WNP) from Polygonatum sibiricum against the Aβ25–35 -induced neurotoxicity in PC12 cells and explored the underlying mechanism. The results showed that pretreatment with PS-WNP significantly attenuated cell death and the elevated Bax/Bcl-2 ratio evoked by Aβ25–35, and subsequently inhibited mitochondrial dysfunction and cytochrome c release into the cytosol. Moreover, PS-WNP significantly inhibited Aβ25–35 induced caspase-3 activation and enhanced the protein levels of phosphorylated Akt (p-Akt) in PC12 cells. Additionally, pretreatment with the PI3K inhibitor (LY294002) completely abolished the protective effects of PS-WNP against Aβ25–35 -induced neuronal cell apoptosis. These observations unambiguously suggested that the protective effect of PS-WNP against Aβ25–35 -induced apoptosis in PC12 cells was associated with the enhancement of PI3K/Akt signaling pathway.